2004
DOI: 10.1113/expphysiol.2003.026609
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation between the time courses of femoral artery blood flow and pulmonary V̇O2 during repeated bouts of heavy knee extension exercise in humans

Abstract: It has frequently been demonstrated that prior heavy cycling exercise facilitates pulmonarẏ VO 2 kinetics at the onset of subsequent heavy exercise. This might be due to improved muscle perfusion via acidosis-induced vasodilating effects. However, it is difficult to measure the blood flow (BF) to the working muscles (via the femoral artery) during cycling exercise. We therefore selected supine knee extension (KE) exercise as an alternative, and investigated whether the fasterVO 2 kinetics in the 2nd bout was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
54
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(65 citation statements)
references
References 48 publications
(81 reference statements)
10
54
1
Order By: Relevance
“…These findings are consistent with previous studies examining prior exercise in both young and older adults and suggest a greater muscle perfusion prior to and throughout Mod 2 (12,22,24). A greater muscle oxygenation is consistent with previous demonstrations of elevated HR in older adults (12,51) and greater limb conduit artery blood flow in young adults (16,17,41) during baseline exercise following heavy-intensity exercise and very early in the transition to a subsequent bout of exercise. There is evidence that O 2 availability is impaired during the transition to exercise in muscle from older animals and human subjects (3,11,12,14,39,43,44,49), and thus prior exercise in older adults likely improves O 2 availability in Mod 2 compared with Mod 1 .…”
Section: Discussionsupporting
confidence: 82%
“…These findings are consistent with previous studies examining prior exercise in both young and older adults and suggest a greater muscle perfusion prior to and throughout Mod 2 (12,22,24). A greater muscle oxygenation is consistent with previous demonstrations of elevated HR in older adults (12,51) and greater limb conduit artery blood flow in young adults (16,17,41) during baseline exercise following heavy-intensity exercise and very early in the transition to a subsequent bout of exercise. There is evidence that O 2 availability is impaired during the transition to exercise in muscle from older animals and human subjects (3,11,12,14,39,43,44,49), and thus prior exercise in older adults likely improves O 2 availability in Mod 2 compared with Mod 1 .…”
Section: Discussionsupporting
confidence: 82%
“…On the other hand, a rapid appearance of phase II of mQ would occur in regions where the early increase in mQ closely matches the dynamics of mV O 2 (i.e., constant deoxy-[HbϩMb]), and thereby a short TD would be followed by a slower (20). The results in the present study support the latter scenario, thus suggesting that the performance of prior heavy exercise would promote the convective delivery of O 2 (phase II mQ ) to multiple sites of the muscles, improving the adequacy of mV O 2 /mQ O 2 matching at the onset of the subsequent bout of exercise (7,9,15,16,22,23,44).…”
Section: Discussionsupporting
confidence: 76%
“…For heavy exercise, comparison of MRT or P of blood flow with previous investigations in humans is not straightforward because we chose to truncate the MRT so as to reflect the primary component of the response, whereas others have included the blood flow increase associated with the V O 2 slow component (1,11,37). The rationale for limiting the calculation of the heavy exercise MRT was that we were interested in determining the relationship between the primary components of the estimated Q cap and V O 2m kinetics.…”
Section: Deoxy-hb As (A-v)omentioning
confidence: 99%
“…The resulting overall Q cap kinetics appeared to be tightly coupled to the temporal profile of V O2m. exercise; skeletal muscle; oxygenation INSIGHTS ON THE CONTROL OF exercising muscle blood flow (Q m ) can be gained from the investigation of its response in the transitional phase (i.e., kinetics) (21, 27), but because of methodological constraints the kinetics of Q m in humans have been studied primarily in larger vessels (1,16,22,31,37,42,44).The difficulty in obtaining measurements with a time resolution that allows reliable kinetic analysis during large muscle mass exercise (e.g., cycling or running) has led to a predominant use of knee extensor or forearm exercise with measurements of blood flow made by Doppler ultrasound (11,22,31,37,42,44). These investigations have shown that the Q m response is biphasic with an initial fast phase determined by the combined effects of muscle contraction (muscle pump) (41) and possibly rapid vasodilation (48) followed by a second slower phase that appears to match O 2 delivery and utilization (43).…”
mentioning
confidence: 99%
See 1 more Smart Citation